Analisis Keterampilan Literasi Digital Mahasiswa dalam Menggunakan Media Sosial Instagram dalam Pembelajaran Bahasa Indonesia - Kristian, Novan (EduInovasi: Journal of Basic Educational Studies, 2024)
This study was conducted to determine the digital literacy skills of students in using Instagram social media in learning Indonesian. This study was conducted using a qualitative descriptive method with a survey technique. The population in this study was the results of filling out a questionnaire distributed via Google Forms. Data collection was carried out by distributing questionnaires via Google Forms to respondents. The results showed that 93.3% of students knew what digital literacy was while 6.6 percent of respondents did not know the definition of digital literacy. Students chose listening skills media on Instagram, which was shown the most, 53.3% on the Reels feature. Students chose the most Live speaking skills media on Instagram, 66.7%. Students chose reading skills media on Instagram, 36.7% on the Post feature and as many as 33.3% chose the Instagram Instastory and Reels features, choosing writing skills. The results showed that most respondents were skilled at using Instagram as a medium for learning Indonesian.